Experimental Study on Friction and Wear Behaviors of Ball Bearings under Gas Lubricated Conditions - Abdollah, Mohd Fadzli; Mazlan, Mohd Afiq Azfar; Amiruddin, Hilmi; Tamaldin, Noreffendy (Universiti Teknologi Malaysia, 2014)
Friction and wear behaviors of ball bearings made from carbon-chrome steel were experimentally simulated using a modified ball-on-disc tribometer. The test was performed over a broad range of applied loads (W), sliding velocities (v) and sliding distances (L) under gas lubricated conditions using a Taguchi method. The results found that gas blown to the sliding surfaces in air effectively reduced the coefficient of friction as compared with the air lubrication at higher applied load, sliding speed and sliding distance. In addition, a specific wear rate is constant throughout the tests under gas lubricated conditions. However, under air lubrication, the specific wear rate decreases with increasing applied load, sliding speed and sliding distance. By using the optimal design parameters, a confirmation test successfully verify the N2-gas lubrication reduced average coefficient of friction and simultaneously improved wear resistance about 24% and 50%, respectively. This is in accordance with a significant reduction of wear scar diameter and smoother worn surface on a ball.